Implementation of Law Number 23 of 2011 on Zakat Management in LazisMU and LazisNU Pati Regency - Fitrah Pangestullah Putra Renjana; M. Junaidi (Universitas Muhammadiyah Surakarta, 2024)
Zakat is one of the pillars in the pillars of Islam which is in third place after prayer, with its existence zakat is one of the supporting pillars for the perfection of Islam. Quality zakat management institutions should be able to manage existing zakat effectively and efficiently, such as LAZISMU and LAZISNU Pati Regency as Amil Zakat Institutions that collect and distribute zakat, infaq and shadaqah. The formulation of the problem in this research is how to manage and supervise fund collection in LAZISMU and LAZISNU Pati Regency and how to manage and supervise zakat in LAZISMU and LAZISNU Pati Regency. So in this case the research aims to describe the management, collection and distribution of zakat as well as the factors inhibiting and encouraging the implementation of zakat carried out at LAZISMU and LAZISNU in Pati. The method used is the empirical juridical method with interview techniques and literature study. The results of this research are that various kinds of supervision and collection are carried out by LAZISMU and LAZISNU Pati with their respective Flagship Programs, and there is a supervisory body that carries out supervisory functions over the collection and distribution of zakat, infaq and shdaqah from external, namely the Ministry of Religion and from Internal in accordance with respective Islamic Community Organizations.